2019
DOI: 10.1371/journal.pgen.1007909
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of DMXL2 in olfactory information transmission and the first wave of spermatogenesis

Abstract: Gonad differentiation is a crucial step conditioning the future fertility of individuals and most of the master genes involved in this process have been investigated in detail. However, transcriptomic analyses of developing gonads from different animal models have revealed that hundreds of genes present sexually dimorphic expression patterns. DMXL2 was one of these genes and its function in mammalian gonads was unknown. We therefore investigated the phenotypes of total and gonad-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…DMXL2 (DmX-like protein 2) encodes a protein with multiple WD40 domains and is involved in many cellular functions, including participating in regulation of insulin secretion and glucose homeostasis [ 46 49 ]. Knockout experiments in mice showed that loss of DMXL2 function triggered severe hypoglycemia and death in neonates [ 46 ]. Further examination of this gene, we found six specific missense mutations with the allele frequency that differed greatly between hyper-arid desert group and semi-desert group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DMXL2 (DmX-like protein 2) encodes a protein with multiple WD40 domains and is involved in many cellular functions, including participating in regulation of insulin secretion and glucose homeostasis [ 46 49 ]. Knockout experiments in mice showed that loss of DMXL2 function triggered severe hypoglycemia and death in neonates [ 46 ]. Further examination of this gene, we found six specific missense mutations with the allele frequency that differed greatly between hyper-arid desert group and semi-desert group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of DMXL2 protein in patients' fibroblasts results in impaired autophagy, and modeling DMXL2 loss in murine neurons recapitulates defective autophagy and affects neurite development and synaptic connectivity (Esposito et al, 2019). While the complete loss of Dmxl2 is embryonically lethal in mice (Tata et al, 2014;Gobé et al, 2019), heterozygous Dmxl2 mice show macrocephaly and corpus callosum dysplasia, confirming the DMXL2 role in brain development (Kannan et al, 2017).…”
Section: Autophagy and Neurodevelopmental Disorder With Epilepsymentioning
confidence: 85%
“…The APH1B gene encodes one of the four subunits of the γ-secretase complex. APH1B plays an important role in the Notch signaling pathway because it stabilizes the complex [ 24 ]. This study appears to be the first report of the involvement of APH1B in feed efficiency in livestock.…”
Section: Discussionmentioning
confidence: 99%